Pengaruh Kepercayaan dan Online Shopping Experience Terhadap Keputusan Pembelian Konsumen Shopee (Studi Kasus pada Mahasiswa Manajemen Universitas Muhammadiyah Bengkulu) - Indah Tri Rahayu; Ade Tiara Yulinda; Ririn Armelinda; Qinasih Wahyono Putri (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to determine Trust and Online Shopping Experience on Shopee Consumer Purchase Decisions in Class of 2019 Students of the Management Study Program, University of Muhammadiyah Bengkulu. The method used is a quantitative method. The population used in this study were 2019 batch students of the Management Study Program at the Muhammadiyah University of Bengkulu who had used the Shopee application. This study used a total sampling technique, namely all members of the population were immediately targeted and research objects. Thus the number of samples is all 2019 Batch Students of Management Study Program, Muhammadiyah University of Bengkulu, namely as many as 181 students as respondents. The data analysis technique in this study is the classical assumption test, multiple linear regression, the coefficient of determination.